Ebstein's Anomaly With Right Atrial Thrombus in 23 Years Old Man at Reference National Teaching Hospital of Ndjamena: A Case Report. - Oumar, Mahamat-Azaki; Abdel-madjid, Zakaria Zakaria; Adam, Ahamat Ali; Lucien, Allawaye; AbdelKerim, Oumkalsoum; Jean, Baptiste Anzouan-Kacou (Journal of Hypertension and Cardiology, 2024)
Ebstein’s anomaly is a rare congenital heart disease. It is usually associated with other congenital defects, particularly atrial septal defect/patent foramen ovale (PFO). We report here the case of Ebstein's disease revealed in a 23-year-old adult admitted for palpitations and exertional dyspnoea. He was in heart failure. The EKG showed atrial flutter . Cardiomegaly was present with a cardiothoracic index of 0.7. On echocardiography, the apical displacement of the tricuspid septal leaflet was 15 mm/m2 , the Celermajer index was Grade 3.  There was a large thrombus floating in the right atrium. While awaiting surgical management, the patient was being treated with diuretics, digitalis and anticoagulants.
Keywords: Ebstein's anomaly; Adult; Congenital Heart Disease; Chad